Therapeutic considerations in acute lymphocytic leukemia. - Holland, J. F. (1978)
Evidence that the first human neoplasm systematically explored with chemotherapeutic treatments has apparently been cured in a palpable segment of affected patients evokes optimism for other types of cancer. The application of similar effort, similar logic, and quantitative experimental therapeutic approaches to the common cancers augurs well for cancer research and clinical medicine.